Atypical evolution of collapsing FSGS in extreme elderly: case report - Romão Fonseca, Aline; Bezerra de Araújo, Flávio; Moura Lima, Ricardo Sammuel (Journal of Health & Biological Sciences, 2024)
Introduction: Segmental and Focal Glomerulosclerosis (FSGS) is an entity characterized by glomerular damage involving the podocyte as the main target. A variant with a worse prognosis, poor response to corticosteroid therapy, and rapid progression to end-stage renal disease is recognized as collapsing FSGS. Case Report: A 102-year-old man with nephrotic syndrome and acute kidney injury underwent renal biopsy, revealing collapsing FSGS. He achieved an excellent response to immunosuppressive treatment, presenting renal recovery, and was discharged from dialysis treatment. Discussion: Diagnosis and definition of treatment in the elderly are challenging, and each case must be individualized and have functionality and risk assessed in a naturally immunosuppressed population.